2021
DOI: 10.3389/fcimb.2021.791466
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and SCFAs Play Key Roles in QingFei Yin Recipe Anti-Streptococcal Pneumonia Effects

Abstract: Emerging evidence has revealed the presence in animals of a bidirectional regulatory “lung-gut axis” that provides resistance to respiratory infections. Clues to the existence of this system stem from observations that respiratory infections are often accompanied by gastrointestinal symptoms, whereby intestinal microbiota appear to play pivotal roles in combating pathogenic infections. Importantly, short-chain fatty acids (SCFAs) produced by the gut microbiota appear to serve as the biological link between hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Another shared differential genus Faecalibacterium is an important intestinal bacterium to produce butyric acid. Butyric acid is a major short-chain fatty acid (SCFA) produced by gut microbiota ( Sun et al., 2021 ). SCFAs are speculated to play an important role in the cross talk between the gut and brain.…”
Section: Discussionmentioning
confidence: 99%
“…Another shared differential genus Faecalibacterium is an important intestinal bacterium to produce butyric acid. Butyric acid is a major short-chain fatty acid (SCFA) produced by gut microbiota ( Sun et al., 2021 ). SCFAs are speculated to play an important role in the cross talk between the gut and brain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SCFAs have been found to act as bidirectional connecting agents between the gut and lung microbiota, which has since led to the discovery of a positive correlation between certain infectious bowel diseases and pulmonary infections and vice versa. 37 Given that m/z 90 was incidentally found to be decreased in both patient groups examined in this study, a possible disturbance in both the gut and lung microbiota may therefore be a confounding variable for the pathogenesis of schizophrenia and MDD. Appropriately, previous studies have indicated that elevated levels of butyric acid had a positive effect on several neurologic and psychiatric pathologies, such as Alzheimer disease, Parkinson disease and autism, as well as E123 schizophrenia and MDD.…”
Section: Discussionmentioning
confidence: 76%
“…Another bacterial taxon distinguishing the FLU group in our study was Faecalibacterium . It is well known that this bacterium is involved in the production of butyric acid, the main SCFA produced by the intestinal flora [ 80 ]. Moreover, in the studies involving patients with major depressive disorder (MDD), this bacterium was identified as a potential MDD biomarker [ 81 ].…”
Section: Discussionmentioning
confidence: 99%